Evaluation of Awareness and Perception of Clear Aligner Orthodontic Treatment Among Students of Hawler Medical University. - Maryam Fouad Bilal; Ahmed Qesim Ali; Layard Khalil Ibrahim (Erbil Dental Journal)
Background and Objectives: The growing emphasis on appearance has led to an increased   interest in orthodontic treatment among adults, particularly those who are highly self-conscious about their looks. Clear Aligner Therapy, a nearly invisible and effective method for aligning teeth, represents the latest generation of aesthetic orthodontic treatments. This study aims to assess the awareness and perception of Clear Aligner Therapy among students at Hawler     Medical University.